SIFAT ARANG EMPAT JENIS KAYU CEPAT TUMBUH DI PROVINSI RIAU SEBAGAI BAHAN BAKU BIOENERGI (BIO BRIKET): The Properties of Charcoal from Four Types of Fast Growing Wood In Riau Province As A Bioenergy Raw Material (Bio-Briquette) - Yanti, Rina Novia; Pari, Gustan; Dinata, Marta; Al Amady, M. Rawa; Suryanti (Jurnal Penelitian Hasil Hutan, 2024)
The availability of fossil energy will increasingly become scarce. For this reason, alternatives are being sought to use biomass as a renewable energy source. The fast-growing types of wood in Riau Province, namely ketapang (Terminalia catappa L), mahang (Macaranga spp), simpur (Dillenia indica.L), dan pulai (Alstonia spp) have not been utilized optimally. Fast growing wood is used as raw material for bioenergy, namely biobriquettes. The proximate analysis carried out was to calculate the water content (%), ash content (%), volatile matter content (%), and calorific value (cal/g. The aim of this research was to analyze the characteristics of the proximate test results of four types of fast-growing wood in Riau Province. The results of the research show that the average ash content of the charcoal is 0.36% according to SNI 01-6235 of 2000, the maximum is 8%. The volatile matter content of charcoal material is 14,5%, making bio briquettes the average volatile matter content value is 12,95% already meets SNI, a maximum of 15%. The average calorific value of raw materials is 4,069 cal/g and after it becomes a product the calorific value becomes 6,368 cal/g, which is set at a minimum of 5000 cal/g. In general, four types of wood grow quickly in the province Riau is recommended as a bio-energy raw material because it meets SNI 01-6235 of 2000.